PAS Domain of the Aer Redox Sensor Requires C-Terminal Residues for Native-Fold Formation and Flavin Adenine Dinucleotide Binding - Herrmann, Sarah (American Society for Microbiology, 2004)
The Aer protein in Escherichia coli is a membrane-bound, FAD-containing aerotaxis and energy sensor that putatively monitors the redox state of the electron transport system. Binding of FAD to Aer requires the N-terminal PAS domain and residues in the F1 region and C-terminal HAMP domain. The PAS domains of other PAS proteins are soluble in water. To investigate properties of the PAS domain, we subcloned segments of the aer gene from E. coli that encode the PAS domain with and without His(6) tags and expressed the PAS peptides in E. coli. The 20-kDa His(6)-Aer(2-166) PAS-F1 fragment was purified as an 800-kDa complex by gel filtration chromatography, and the associating protein was identified by N-terminal sequencing as the chaperone protein GroEL. None of the N-terminal fragments of Aer found in the soluble fraction was released from GroEL, suggesting that these peptides do not fold correctly in an aqueous environment and require a motif external to the PAS domain for proper folding. Consistent with this model, peptide fragments that included the membrane binding region and part (Aer(2-231)) or all (Aer(2-285)) of the HAMP domain inserted into the membrane, indicating that they were released by GroEL. Aer(2-285), but not Aer(2-231), bound FAD, confirming the requirement for the HAMP domain in stabilizing FAD binding. The results raise an interesting possibility that residues outside the PAS domain that are required for FAD binding are essential for formation of the PAS native fold.